Making and testing laboratory laminated veneer lumber: an illustrated guide - Liew, Kang Chiang (LAP Lambert Academic Publishing, 2011)
Laminated veneer lumber is a product made from pieces of veneers put together on top of each other with their grains aligned parallel to each other and then glued together. This simple step-by-step illustrated guide book could be used by students in their learning or even researches to conduct their experiments or research works. With the many images presented, it would help people with little knowledge of making laminated veneer lumber on a laboratory scale to make one themselves. The processes described in this guide start from harvesting of logs, preparing them for peeling into veneers, drying, cutting test pieces from the fabricated laminated veneer lumber for physical and mechanical testing according to different standards, conducting the testing and calculating the data obtained from the testing.